Evaluation of harvesting energy from pedestrians using piezoelectric floor tile energy harvester - Yingyong, Phonexai; Thainiramit, Panu; Jayasvasti, Subhawat; Thanach-Issarasak, Nicharas; Isarakorn, Don (My University, 2021)
This study determined the influences of several pedestrian parameters on the amount of energy harvested by a piezoelectric energy harvesting floor tile (EHFT), for the goal of providing a realistic harvested energy specification for an application in a certain pedestrian environment. Experiments were conducts to measure the original harvested energy in a laboratory and the harvested energy under a variety of pedestrian parameter values. The main outcomes were the following: the original, unadjusted harvested energy provided by one pedestrian step obtained in the laboratory was 35 mWrms; when ten people, weighing less than 50 kg or over 70 kg, stepped on the floor tile, the harvested energy was about 11.0 mJ and 32.0 mJ, respectively; When 30 people walked or ran over it without any fixed pattern, the harvested energy was about 289.0 mJ and 736.9 mJ, respectively; when 30 people walking in a row, separated by a gap of 0.5, 1, and 1.5 m, walking over the tile one by one, the stored energy was 401.0 mJ, 406.0 mJ, and 452.0 mJ, respectively. To conclude, two pedestrian parameters affected the harvested energy strongly pedestrian body weight and pace (walking or running), but pedestrian density did not affect the harvested energy of our developed EHFT strongly. Therefore, in an adjustment of a laboratory-obtained harvested energy into a realistic specification, the influences of those two pedestrian parameters had to be included, while pedestrian density could be ignored. These findings should be directly useful to new researchers and developers in their effort to formulate a realistic harvested energy specification for their developed EHFT.
Keywords: Direct force excitation; Electric generator; Energy harvester; Floor tiles; Frequency up-conversion; Low-vibration harvester; Piezoelectric